Viscosity approximation involving generalized cocoercive mapping in Hadamard space - Ali, Bashir; Nuhu, Abdulnasir Bala (Modern Mathematical Methods, 2025)
In this paper, we introduce a new type of mapping which we term generalized cocoercive mapping in a \(CAT(0)\) space, we prove some properties of the new mapping, we also construct implicit viscosity type algorithm for approximating common solution of fixed point of \((f, g)\)-generalized \(κ\)-strictly pseudononspreading mapping, quasinonexpansive mapping, family of \(θ_i\)-generalized demimetric mapping, mixed equilibrium problem and variational inequality problem involving the new mapping. Strong convergence is obtained under some mild conditions and without considering cases as in many results in the literature. Our results improved and generalized many results in the literature and our technique of proof is new and of independent interest.